Regression Modeling of the Effect of Chip Slenderness Ratio and Cutting Parameters on Vibration - ADIYAMAN, Oktay (Gazi Üniversitesi Fen Bilimleri Dergisi, 2021)
Chip slenderness ratio, which is defined as the ratio of depth of cut to feed rate in turning processes, is an subject that has been studied. For this reason, the chip slenderness ratio should be examined from different aspects. In this paper, different cutting parameters (feed rate, depth of cut) were selected together with chip slenderness ratio by using tools with three different tool approach angles as 15, 30 and 45 degree in turning AISI 1050 steel. As a result, a regression model was created to determine the effect of feed rate, depth of cut, tool approach angle and chip slenderness ratio on vibration in all three directions. In all experimental studies, depth of cut and feed rate were selected as cutting parameters. 5 different chip slenderness ratio were created (1, 3, 5, 10 and 15) and the vibrations in the turning were measured in three directions (X, Y, Z). Depending on the vibration, regression models were created in all three directions for the chip slenderness ratio and cutting parameters. The SPSS V24 program was used for regression models and statistical analysis. In the regression models, it was seen that the greatest effect in all three directions (X, Y and Z) was the feed rate, depth of cut and tool approach angle, respectively, and a significant model could not be created regarding the chip slenderness ratio. In addition, it was determined that the greatest vibration values occurred in the direction of feed rate (Y direction). In cases where chip slenderness ratio is 1 and 10, minimum vibration values were measured in all directions (X, Y and Z) and tool approach angles. When the tool approach angle is 30 degree, the most stable vibration values were occurred. Tornalama işlemlerinde talaş derinliğinin ilerleme hızına oranı olarak tanımlanan talaş incelme oranı, üzerinde çalışılan bir konudur. Bu nedenle konunun farklı yönlerden ele alınarak incelenmesi gerekmektedir. Bu çalışmada AISI 1050 çeliğinin tornalanmasında 15, 30 ve 45 derece olacak şekilde üç farklı takım yaklaşma açısına sahip takım kullanılarak farklı kesme parametrelerinin (ilerleme değeri, talaş derinliği) talaş incelme oranı ile birlikte değerlendirilmesi yapılmıştır. Bunun sonucunda ilerleme değeri, talaş derinliği, yaklaşma açısı ve talaş incelme oranının her üç yöndeki titreşime etkisinin belirlenmesi için regresyon modeli oluşturulmuştur. Tüm deneysel çalışmalarda kesme parametreleri olarak talaş derinliği ve ilerleme değeri seçilmiştir. 5 farklı talaş incelme oranı oluşturulmuş (1, 3, 5, 10 ve 15) ve işlemedeki titreşimler üç doğrultuda (X, Y, Z) ölçülmüştür. Titreşime bağlı olarak talaş incelme oranı ve kesme parametrelerine ait her üç yönde regresyon modelleri oluşturulmuştur. Regresyon modelleri ve istatistiksel analizler için SPSS V24 programı kullanılmıştır. Uygulanan regresyon modellerinde her üç yönde de (X, Y ve Z) en büyük etkinin sırasıyla ilerleme değeri, talaş derinliği ve yaklaşma açısı olduğu görülmüş, talaş incelme oranı ile ilgili anlamlı bir model oluşturulamamıştır. Ayrıca en büyük titreşim değerlerinin ilerleme yönünde (Y yönü) meydana geldiği tespit edilmiştir. Talaş incelme oranının 1 ve 10 olduğu durumlarda tüm yönlerde (X, Y ve Z) ve yaklaşma açılarında minimum titreşim değerleri ölçülmüştür. Talaş yaklaşma açısının 30 derece olduğu durumlarda en stabil titreşim değerleri elde edilmiştir.